2013
DOI: 10.3348/kjr.2013.14.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists' Performance for Detecting Lesions and the Interobserver Variability of Automated Whole Breast Ultrasound

Abstract: ObjectiveTo compare the detection performance of the automated whole breast ultrasound (AWUS) with that of the hand-held breast ultrasound (HHUS) and to evaluate the interobserver variability in the interpretation of the AWUS.Materials and MethodsAWUS was performed in 38 breast cancer patients. A total of 66 lesions were included: 38 breast cancers, 12 additional malignancies and 16 benign lesions. Three breast radiologists independently reviewed the AWUS data and analyzed the breast lesions according to the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
(43 reference statements)
2
35
2
1
Order By: Relevance
“…Se sabe que el tumor de células gigantes de mano y muñeca es hipoecogénico 12 , con un aumento de vascularización, por lo que se ha considerado que la ecografía asociada con doppler podría aportar información diagnóstica sobre el mismo 13 . En nuestra revisión la capacidad diagnóstica de la ecografía es baja a pesar de la mejoría técnica de los equipos, posiblemente porque se trata de una prueba observador dependiente 14 .…”
Section: Discussionunclassified
“…Se sabe que el tumor de células gigantes de mano y muñeca es hipoecogénico 12 , con un aumento de vascularización, por lo que se ha considerado que la ecografía asociada con doppler podría aportar información diagnóstica sobre el mismo 13 . En nuestra revisión la capacidad diagnóstica de la ecografía es baja a pesar de la mejoría técnica de los equipos, posiblemente porque se trata de una prueba observador dependiente 14 .…”
Section: Discussionunclassified
“…Several studies have concluded that the sensitivity, diagnostic performances, and image quality of AWUS and HHUS are equivalent [15161718192021]. However, these studies have primarily evaluated mass lesions in the breast.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these concerns may be alleviated with the use of new automated whole-breast ultrasound systems. 35,41,[43][44][45][46][47][48][49][50] There is also strong support for MRI, [51][52][53][54][55][56][57][58] but there remain concerns about the use of contrast agents, its cost and its availability, although accelerated breast MRI sequences are being trialed. [59][60][61][62][63][64][65][66][67][68][69] Finally, molecular breast imaging is being touted for extremely dense breasts, [70][71][72][73][74][75][76][77][78] although concerns persist about dose and contrast; nonetheless, these concerns are starting to be addressed.…”
Section: Introductionmentioning
confidence: 99%